2011
DOI: 10.1124/dmd.111.040121
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pathway of Metabolic Activation of Bisphenol A-Related Compounds for Estrogenic Activity

Abstract: ABSTRACT:We previously demonstrated that estrogenic activity of bisphenol A (BPA) in the yeast estrogen screening assay was increased severalfold after incubation with rat liver S9 fraction in the presence of a NADPH-generating system. In this study, we investigated whether eight BPA-related compounds are similarly activated metabolically by rat liver S9 fraction. Three of the analogs exhibited an increase of estrogenic activity after incubation with rat liver S9 fraction but not with microsomal or cytosolic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…This is possibly due to decreased epithelial thickness ( t ; Figure 4G) in the BPA late exposure group, when the mucous cells make up a higher percentage of a thinner epithelium. The effects of BPA exposure on Muc5B may be due to the binding of the parent molecule or its metabolites to estrogen receptors (Okuda et al 2011). Estrogen (17β-estradiol) is known to induce Muc5B expression in airway epithelial cells (Choi et al 2009) via estrogen receptor-α.…”
Section: Discussionmentioning
confidence: 99%
“…This is possibly due to decreased epithelial thickness ( t ; Figure 4G) in the BPA late exposure group, when the mucous cells make up a higher percentage of a thinner epithelium. The effects of BPA exposure on Muc5B may be due to the binding of the parent molecule or its metabolites to estrogen receptors (Okuda et al 2011). Estrogen (17β-estradiol) is known to induce Muc5B expression in airway epithelial cells (Choi et al 2009) via estrogen receptor-α.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro study using murine cells, exposure to BPA at concentrations ranging from 10 −10 to 10 −8 M (approximately 0.023 to 2.3 ng ml -1 ) markedly induced spermatogonial proliferation (Sheng & Zhu 2011). Acute toxicity, genotoxicity and estrogenic activity of BPS, BPB and BPF have been reported (Chen et al 2002;Rivas et al 2002;Okuda et al 2011;Pisapia et al 2012). One study showed that exposure to BPAF considerably reduced testosterone levels in adult male rats (Feng et al 2012).…”
Section: Please Scroll Down For Articlementioning
confidence: 95%
“…BPA can be glucuronided by microsomal UGT2B1, which is an isoform of UDP-glucuronosyltransferase (UGT)1718. It has been suggested that metabolic activation to MBP may occur in the detoxification pathway of BPA when glucuronidation cannot work efficiently, although the MBP metabolic activation may not be significant under usual circumstances19. Previous study has shown that the MBP metabolic activation can occur in the rat fetal livers18.…”
Section: Discussionmentioning
confidence: 99%